Micro-parameter Optimization of Helical Cylindrical Gear based on Romax - Hongfu Xing; Chaohui Yang; Nan Yu; Chao Xu; Jingliang Jiang (Jixie chuandong)
With the development of technology，the high precision transmission equipment has higher and higher requirements on gear. In the gearbox of main reduction helical cylindrical gear as the research object，by using Romax software，the gearbox model is established，combining the theory of microscopic parameters optimization of cylindrical bevel wheel，the transmission error，distribution of load per unit length of gear tooth surface and the contact spot are taken as the optimization objectives for microscopic gear modification，an omnidirectional modification method combining helical modification and tooth profile modification is proposed. By comparing the goal of the optimization of the gear parameters before and after modification，reduce the optimized transmission error and tooth surface load distribution more uniform，good contact spots，improve the gear meshing，improve the service life of the gear.